FUNGSI MUSIK DALAM TARI KEJEI DI KABUPATEN REJANG LEBONG PROVINSI BENGKULU - zainal, nurzena aprilia; Supriadi, Didin; S, Saryanto (Program Studi Pendidikan Musik, 2022)
Abstract: Kejei dance is one of the cultures of the Rejang Lebong people, in which there are several elements, one of which is music. Music in the kejei dance has its own function. This study provides a new knowledge about the function of music in the kejei dance in Rejang Lebong Regency, Bengkulu.The method used in this study is a descriptive qualitative method. Data was collected by means of (1) offline observation, (2) interviews, (3) documentation. While the data analysis technique is done by data reduction, data display, conclusion drawing/drawing conclusions.The results obtained: The function of music in the Kejei dance is 1) the function of music as an accompaniment to the opening motion or prayer movement, 2) the content movement or the eye movement of the oars, and 3) the closing motion with three different patterns, namely (a) the pattern of sea waves, (b) ) lanting bird pattern, (c) gibbon pattern behind the hill), 4) music as a dance atmosphere, 5) music as an illustration.